2013
DOI: 10.1371/journal.pone.0069355
|View full text |Cite
|
Sign up to set email alerts
|

Simple System for Isothermal DNA Amplification Coupled to Lateral Flow Detection

Abstract: Infectious disease diagnosis in point-of-care settings can be greatly improved through integrated, automated nucleic acid testing devices. We have developed an early prototype for a low-cost system which executes isothermal DNA amplification coupled to nucleic acid lateral flow (NALF) detection in a mesofluidic cartridge attached to a portable instrument. Fluid handling inside the cartridge is facilitated through one-way passive valves, flexible pouches, and electrolysis-driven pumps, which promotes a compact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 46 publications
(50 reference statements)
0
75
0
1
Order By: Relevance
“…In contrast, of those anti-HIV repeat reactive samples that tested NAAT nonreactive and Western blot negative or indeterminate, 98.5% had an Abbott ELISA signal-cutoff ratio less than 15 [15]. The need for an optimized and realistic algorithm and pool size that is cost effective, for different settings and incidences via-as-vis methodology (such as hard spinning), taking into account HIV 1 genetic diversity, primerprobe mismatch and platforms as summarized in Table 6 below, cannot be over emphasized [16][17][18][19][20][21][22][23]26,27,[36][37][38][39][40][41][42][43][44][45]. Cannillo et al recently, reported that CAD as the most frequent cardiac complication in HIV patients (particularly those with low CD4 and high viral load) treated with HAART.…”
Section: Need For Population Specific Screening Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, of those anti-HIV repeat reactive samples that tested NAAT nonreactive and Western blot negative or indeterminate, 98.5% had an Abbott ELISA signal-cutoff ratio less than 15 [15]. The need for an optimized and realistic algorithm and pool size that is cost effective, for different settings and incidences via-as-vis methodology (such as hard spinning), taking into account HIV 1 genetic diversity, primerprobe mismatch and platforms as summarized in Table 6 below, cannot be over emphasized [16][17][18][19][20][21][22][23]26,27,[36][37][38][39][40][41][42][43][44][45]. Cannillo et al recently, reported that CAD as the most frequent cardiac complication in HIV patients (particularly those with low CD4 and high viral load) treated with HAART.…”
Section: Need For Population Specific Screening Algorithmsmentioning
confidence: 99%
“…One of these universal platforms has tested 19 pools of 10 plasma samples from West Africa and recorded a high sensitivity. This simple, rapid, and robust test format at reduced cost is valuable for the screening of blood samples by laboratory workers in blood banks or diagnostic laboratories in developing countries [20,36]. These assays are aimed at increasing analytical sensitivity breaking the antigen-antibody complex and reducing the window period at low cost.…”
Section: Application Of Dipstick Naat Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Pouch chips are an attractive design option for autonomous microfluidic devices, providing a means for fluid storage (reservoirs), fluid actuation (pumping), and flow control (valving) [7][8][9][10]. By attaching or laminating flexible polymer sheet materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sheet can also be used to realize diaphragm valves that constrict flow in channels or seal chambers for processing. Chip design, materials, fabrication, and accompanying instrumentation and actuators are presented in detail [8][9][10].…”
Section: Introductionmentioning
confidence: 99%